2013
DOI: 10.1007/s00405-013-2362-y
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and effects on quality of life of liposomal nasal spray treatment compared to nasal ointment containing dexpanthenol or isotonic NaCl spray in patients with rhinitis sicca

Abstract: This study aimed to investigate symptom reduction via the liposomal nasal spray LipoNasal (LN) in patients with rhinitis sicca. Tolerability and the impact on quality of life were also examined. The same parameters were established in parallel for treatment approaches with Bepanthen (BP) nasal ointment containing dexpanthenol and the Rhinomer (RH) nasal spray containing NaCl. This prospective, controlled, open-label observation study was a multicenter trial. 92 patients with rhinitis sicca were allocated to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…The randomised design, the inclusion of several study centres throughout Germany and the study conduction over a period of one year should have limited seasonal and regional factors, however. Taking a closer look at the previously performed studies cited above, it becomes apparent that out of these four trials, only Hahn et al [34] evaluated an isotonic saline solution based on seawater, meanwhile Kehrl and Sonnemann [37] , Oysu et al [38] and Johnsen et al [39] compared the effects of isotonic sodium chloride solutions versus other nasal products. Meanwhile Hahn et al reported positive results for the saline solution tested, the latter three authors observed poor effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The randomised design, the inclusion of several study centres throughout Germany and the study conduction over a period of one year should have limited seasonal and regional factors, however. Taking a closer look at the previously performed studies cited above, it becomes apparent that out of these four trials, only Hahn et al [34] evaluated an isotonic saline solution based on seawater, meanwhile Kehrl and Sonnemann [37] , Oysu et al [38] and Johnsen et al [39] compared the effects of isotonic sodium chloride solutions versus other nasal products. Meanwhile Hahn et al reported positive results for the saline solution tested, the latter three authors observed poor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary endpoints: Clinical symptoms recorded for assessment of the primary endpoint were also evaluated as single items for each nasal spray. Furthermore, a sum score was built from parameters dry nose, impairment of nasal breathing/nasal obstruction and crusting in accordance to a recent publication [34] .…”
Section: Efficacy and Safety Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is not surprising that alternatives to the alpha-sympathomimetic drugs have been sought for a long time. Our group thoroughly investigated the effects and the tolerability of liposomal nasal sprays and ectoine-containing nasal sprays in several clinical trials [ 21 , 30 35 ]. We found that both preparations were comparably effective and low in side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The same superiority was found for nasal irritation, and the recovery time was significantly reduced by about 40%, which appears to be a clinically relevant reduction. Comparing a liposomal nasal spray with an ointment containing dexpanthenol but no decongestant and with an isotonic sodium chloride spray in rhinitis sicca patients, Hahn et al found that, concerning the nasal moisturization, the liposomal spray was evaluated better than dexpanthenol and the isotonic spray [ 21 ]. We reckon that the efficacy and tolerability of a liposomal spray is good compared to generally recognized treatments of rhinitis sicca with nasal ointments containing dexpanthenol alone and with isotonic nasal sprays.…”
Section: Nasal Decongestants In Acute Rhinitismentioning
confidence: 99%